{2-[(η(5)-Cyclopentadienyl)diphenylmethyl]-1H-imidazolido-κN}bis(N,N-diethylamido)titanium(IV) - Cai, Xianfeng (International Union of Crystallography, 2011)
The chemically achiral title molecule, [Ti(C(4)H(10)N)(2)(C(21)H(16)N(2))], crystallizes in the chiral space group P2(1). All three N atoms coordinating to the Ti(IV) atom adopt planar environments [sums of valence angles = 359.5 (6), 360.0 (7) and 360.0 (6)°], which is indicative of pπ–dπ donation from all of these N atoms to the metal and, thus, of the formal 18 e(−) nature of the complex. The overall coordination about the Ti(IV) atom is distorted tetrahedral, assuming the cyclopentadienyl ring occupies one coordination site. The Ti—N(imidazole) amide-type bond is longer by approximately 0.16 Å than the other two Ti—N(amide) bonds.